Sonderangebote und psychologische Preissetzung im deutschen Lebensmitteleinzelhandel; Price Promotions and Psychological Pricing in German Grocery Retailing - Angela Hoffmann; Kerstin Hackelbusch (German Journal of Agricultural Economics (GJAE), 2013)
– Price promotions play a prominent role in German grocery retailing. Their purpose is to increase store traffic and strengthen customer loyalty. It is hypothesized that other marketing tools, like psychological pricing can add to the positive impact of price promotions on sales. Thus, we investigate the joint impact of price promotions and different pricing points on sales. Our empirical analysis shows that just-below prices tend neither to raise sales of regularly priced products nor of price promoted products. The only exception is significant price reductions combined with 99 ending prices (especially of private labels). While our results show no alternatives to regular 9 ending prices, price promotions should rather end in a 99 or be round. Moreover, repdigits (eye-catching price figures) can significantly increase sales of price promoted manufacturers' labels when other cues of price promotions exist. However, German retailers, particularly discount stores, do rarely make use of such combined marketing tools. The results indicate that consumers pay less attention to the size of price reductions than to other cues of price promotions or displays, whereby psychological pricing can intensify the impact of other marketing tools on sales.
Keywords: 330; Sonderangebot; Einzelhandelspreis; Konsumentenverhalten; Werbewirkung; Lebensmitteleinzelhandel; Deutschland